PERAN KEUNGGULAN BERSAING DALAM MEMEDIASI PENGARUH SUMBERDAYA TIDAK BERWUJUD TERHADAP KINERJA PEMASARAN - Sukrin, Sukrin; Haryanto, Abel (Politeknik Negeri Ambon, 2023)
The purpose of this research is to identify and explain the role of competitive advantage in mediating the effect of intangible resources on marketing performance. The total population in this study amounted to 82 employees of the Regional Development Bank of Southeast Sulawesi from 82 sub-branch offices/cash offices spread across 17 districts/cities. Then the sampling technique uses a saturated sample. Data collection techniques using questionnaires or questionnaires that have been tested for validity and reliability. For data processing using the SmartPLS version 3.0 analysis tool. The results of the study show that intangible resources have a significant effect on marketing performance. Intangible resources have a significant effect on competitive advantage. competitive advantage has a significant effect on marketing performance. competitive advantage is able to significantly mediate the effect of intangible resources on marketing performance